Stretchable electrode and preparation method and application thereof
A stretchable electrode with a nanofiber and liquid metal layer structure, enhanced by an adhesive gel, addresses adhesion and processing complexity issues, offering superior stretchability and conductivity on irregular surfaces with low costs.
Patent Information
- Application Number
- CN202411497519.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2024-12-31
AI Technical Summary
Current stretchable electrodes based on paper-kirigami structures face issues with soft conformability, resistance stability, adhesion, and high processing complexity, limiting their application to irregularly shaped objects.
A stretchable electrode composed of a first flexible nanofiber layer, a liquid metal layer, and a second flexible nanofiber layer with an adhesive soft gel at the nodes, forming a paper-cut structure, which enhances stretchability, adhesion, and conductivity while simplifying the manufacturing process.
The electrode exhibits excellent stretchability, softness, and adhesion, maintaining conductive stability on irregular surfaces with a simple and cost-effective production method.
Smart Images

Figure CN119230163A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of flexible electronic devices, and in particular to a stretchable electrode and a preparation method and application thereof. Background Art
[0002] Paper-kirigami structure is one of the more commonly used strategies in the design of stretchable electrodes. By constructing paper-kirigami structure, the stretchability and stability of the electrode can be greatly enhanced. However, the currently developed stretchable electrodes based on paper-kirigami structure usually use PDMS, ECOFLEX, silicone rubber, paper, etc. as substrate materials, and conductive ink, metal, etc. as conductive interconnect materials. The combination of such materials does not have good enough soft conformability and resistance stability, and their processing often involves micro-nano processing, sputtering and spraying, etc., which leads to the complexity of processing technology and steps, and high processing costs. At the same time, this type of paper-kirigami structure stretchable electrode also lacks good adhesion, so it cannot be firmly adhered to the surface of various irregularly shaped objects and follow their movement, which greatly limits their scope of application and effect. Summary of the invention
[0003] Based on this, it is necessary to provide a stretchable electrode and its preparation method and application to address the above problems. The stretchable electrode has excellent stretchability, softness and adhesion, can be firmly adhered to the surface of various irregularly shaped objects and follow their movement, ensuring the conductive stability of the stretchable electrode, and the preparation method is simple and the production cost is low.
[0004] A stretchable electrode, comprising a first flexible nanofiber layer and a liquid metal layer and a second flexible nanofiber layer stacked in sequence on the surface of the first flexible nanofiber layer, the stretchable electrode being a paper-cut structure, an adhesive soft gel being provided at the nodes of the paper-cut structure, and the adhesive soft gel being embedded in the surface of the second flexible nanofiber layer.
[0005] In one embodiment, the thickness of the first flexible nanofiber layer is 40 μm-100 μm;
[0006] And / or, the thickness of the second flexible nanofiber layer is 40 μm-100 μm;
[0007] And / or, the thickness of the liquid metal layer is 3 μm-4 μm.
[0008] In one embodiment, the first flexible nanofiber layer and the second flexible nanofiber layer are independently selected from any one of a thermoplastic polyurethane nanofiber layer and a styrene-butadiene-styrene block copolymer nanofiber layer;
[0009] And / or, the liquid metal layer is selected from a gallium-based liquid metal layer;
[0010] And / or, the adhesive soft gel is selected from at least one of organic silicone gel, RTVS6100 silicone gel, Caster1010 silicone gel or Hengnian 901 silicone gel.
[0011] In one embodiment, the paper-cut structure is an array structure in the shape of a straight line, an array structure in the shape of a propeller, or an array structure in the shape of an arc.
[0012] A method for preparing the stretchable electrode as described above comprises the following steps:
[0013] forming a liquid metal layer and a second flexible nanofiber layer in sequence on the surface of the first flexible nanofiber layer to obtain a composite layer;
[0014] Processing the composite layer into a paper-cut structure;
[0015] An adhesive soft gel is constructed at the nodes of the paper-cut structure so that the adhesive soft gel is embedded on the surface of the second flexible nanofiber layer to obtain a stretchable electrode.
[0016] In one embodiment, the method for preparing the composite layer comprises the following steps:
[0017] Spinning the first spinning solution by electrospinning technology to form a first flexible nanofiber layer;
[0018] attaching liquid metal to the surface of the first flexible nanofiber layer to form a liquid metal layer;
[0019] The second spinning solution is spun on the surface of the liquid metal layer by using electrostatic spinning technology to form a second flexible nanofiber layer to obtain the composite layer.
[0020] In one embodiment, in the step of spinning the first spinning solution using electrospinning technology to form a first flexible nanofiber layer, the electrospinning parameters include: an applied positive voltage of 10kV-20kV, an applied negative voltage of -1kV to -8kV, a drum speed of 200rpm-1500rpm, a liquid supply rate of 0.05mL / min-0.07mL / min, a distance between the needle and the collecting device of 12cm-18cm, a temperature of 25℃-35℃, and an ambient relative humidity of 35%-50%;
[0021] And / or, the mass volume ratio of the first spinning solution is 18%-26%, and the first spinning solution is selected from at least one of a thermoplastic polyurethane solution and a styrene-butadiene-styrene block copolymer solution.
[0022] In one embodiment, in the step of spinning the second spinning solution on the surface of the liquid metal layer using electrospinning technology to form a second flexible nanofiber layer, the electrospinning parameters include: an applied positive voltage of 10kV-20kV, an applied negative voltage of -1kV to -8kV, a drum speed of 200rpm-1500rpm, a liquid supply rate of 0.05mL / min-0.07mL / min, a distance between the needle and the collecting device of 12cm-18cm, a temperature of 25℃-35℃, and an ambient relative humidity of 35%-50%;
[0023] And / or, the mass volume ratio of the second spinning solution is 18%-26%, and the second spinning solution is selected from at least one of a thermoplastic polyurethane solution and a styrene-butadiene-styrene block copolymer solution.
[0024] In one embodiment, in the step of processing the composite layer into a paper-cut structure, the composite layer is cut into the paper-cut structure by using a laser cutting technology according to a set paper-cut structure;
[0025] And / or, in the step of constructing an adhesive soft gel at the nodes of the paper-cut structure, an adhesive soft gel precursor solution is placed at the nodes of the paper-cut structure and cured to form an adhesive soft gel, wherein the curing temperature is 70°C-90°C and the curing time is 10min-20min.
[0026] An application of the stretchable electrode as described above in wearable electronic products, electronic skin or soft robots.
[0027] The stretchable electrode of the present invention is a sandwich structure, which is composed of a first flexible nanofiber layer and a liquid metal layer and a second flexible nanofiber layer sequentially stacked on the first flexible nanofiber layer, so that the stretchable electrode as a whole has good stretchability and flexibility; at the same time, the stretchable electrode is a paper-cut structure, which further improves the stretchability of the stretchable electrode, better reduces the tensile stress of the stretchable electrode and the resistance change during the stretching process, improves the stretching stability, and better realizes multi-directional stretchability, and better ensures the conductive stability of the stretchable electrode; in addition, an adhesive soft gel is provided at the node of the paper-cut structure, and the adhesive soft gel is embedded in the surface of the second flexible nanofiber layer, so that the stretchable electrode has excellent adhesion without affecting its own tensile performance, and at the same time, under the coordinated cooperation of the first flexible nanofiber layer, the second flexible nanofiber layer and the liquid metal layer, the stretchable electrode can be conformally and firmly attached to the surface of various irregularly shaped objects without affecting the movement of the attached objects; moreover, the stretchable electrode of the present invention has a simple structure, a simple processing process and a low manufacturing cost.
[0028] Therefore, the stretchable electrode of the present invention has excellent stretchability, softness and adhesion, and can be conformally and firmly attached to the surface of various irregularly shaped objects and follow their movement, ensuring the conductive stability of the stretchable electrode. At the same time, the preparation method is simple and the production cost is low. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0030] Figure 1 The figure is a picture and a schematic diagram of the structure of the stretchable electrode of the present invention, wherein, in the figure, A represents the first flexible nanofiber layer, B represents the liquid metal layer, C represents the second flexible nanofiber layer, and D represents the adhesive soft gel;
[0031] Figure 2 It is a schematic diagram of an array structure in which the paper-cut structure in the present invention is in a straight line shape;
[0032] Figure 3 It is a schematic diagram of the paper-cut structure in the application example 1 of the present invention;
[0033] Figure 4 This is a picture of a liquid gallium-indium alloy layer formed on the surface of the first flexible nanofiber layer in Example 1 of the present invention, wherein in the figure, A represents the first flexible nanofiber layer, and B represents the liquid gallium-indium alloy layer;
[0034] Figure 5 This is a scanning electron microscope image of the adhesive soft gel embedded in the second flexible nanofiber layer in Example 1 of the present invention, wherein in the figure, C represents the second flexible nanofiber layer, and D represents the adhesive soft gel;
[0035] Figure 6 This is a stress-strain relationship diagram of the stretchable electrode prepared in Example 1 of the present invention;
[0036] Figure 7 A graph showing the relationship between the relative resistance change and the strain of the stretchable electrode prepared in Example 1 of the present invention;
[0037] Figure 8 The stability of the stretchable electrode prepared in Example 1 of the present invention during 3000 cycles of 50% strain stretching;
[0038] Fig. 9The stress-strain relationship diagram of the stretchable electrodes prepared in Examples 1, 4, 5 and 6 of the present invention, wherein in the figure, a represents Example 1, b represents Example 4, c represents Example 5, and d represents Example 6;
[0039] Fig.10 The relative resistance change of the stretchable electrodes prepared in Examples 1, 4, 5 and 6 of the present invention when stretched by 200%, wherein in the figure, a represents Example 1, b represents Example 4, c represents Example 5, and d represents Example 6;
[0040] Fig.11 This is a stress-strain relationship diagram of the stretchable electrode prepared in Comparative Example 1 of the present invention;
[0041] Fig.12 The relative resistance change of the stretchable electrode prepared in Comparative Example 1 of the present invention when stretched by 200%;
[0042] Fig.13 The present invention is an application effect diagram of the stretchable electrode prepared in Application Example 1 being connected to an external circuit, adhering to the surface of a silicone corrugated hose and maintaining conformal adhesion and stable operation during its deformation process; wherein, in the figure, A represents that the stretchable electrode adheres to an irregular silicone corrugated hose surface, B represents that the stretchable electrode can follow the compression of the corrugated hose and maintain adhesion and stable operation, C represents that the stretchable electrode can follow the stretching of the corrugated hose and maintain adhesion and stable operation, and D represents that the stretchable electrode can follow the torsion of the corrugated hose and maintain adhesion and stable operation;
[0043] Fig.14 This is a diagram showing the application effect of the stretchable electrode prepared in Example 1 of the present invention being connected to an external circuit and adhered to the wrist as a flexible heater. DETAILED DESCRIPTION
[0044] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0045] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific implementation methods or embodiments, and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the combinations include any two related listed items, any more related listed items, or all related listed items.
[0046] like Figure 1 As shown, the stretchable electrode provided by the present invention includes a first flexible nanofiber layer and a liquid metal layer and a second flexible nanofiber layer stacked in sequence on the surface of the first flexible nanofiber layer. The stretchable electrode is a paper-cut structure, and an adhesive soft gel is provided at the nodes of the paper-cut structure, and the adhesive soft gel is embedded in the surface of the second flexible nanofiber layer.
[0047] Specifically, the stretchable electrode of the present invention comprises a first flexible nanofiber layer as a flexible base layer, a liquid metal layer as a conductive layer, and a second flexible nanofiber layer as an encapsulation layer, which together form a sandwich structure, wherein the liquid metal layer has excellent softness, ductility, conductivity, safety and stretchability, etc., and cooperates with the first flexible nanofiber layer and the second flexible nanofiber layer to make the stretchable electrode have good stretchability, softness and conductivity.
[0048] Furthermore, the stretchable electrode is a paper-kirigami structure. By utilizing the characteristics of the paper-kirigami structure, the stretchability of the stretchable electrode can be further improved, the tensile stress of the stretchable electrode and the resistance change during the stretching process can be better reduced, and the stretching stability can be improved. For example, the elongation at break of the stretchable electrode of the present invention can be as high as 1085%, and its resistance hardly changes within a strain range of 110%. At the same time, multi-directional stretchability is better achieved, thereby better ensuring the conductive stability of the stretchable electrode.
[0049] Furthermore, an adhesive soft gel is provided at the nodes of the paper-cut structure and embedded in the surface of the second flexible nanofiber layer, so that the stretchable electrode has excellent adhesion without affecting its own stretching properties. At the same time, with the coordinated cooperation of the first flexible nanofiber layer, the second flexible nanofiber layer and the liquid metal layer, the elastic modulus of the stretchable electrode can be approximately 0.0298 MPa, so that the stretchable electrode can be conformally and firmly attached to the surfaces of various irregularly shaped objects without affecting the movement of the attached objects.
[0050] It should be noted that in the present invention, the porosity of the second flexible nanofiber layer is utilized, a portion of the adhesive soft gel is embedded in the second flexible nanofiber layer, and a portion is exposed on the surface of the second flexible nanofiber layer. The adhesive soft gel plays a role similar to a gripper, one side of which can adhere to other objects, and the other side is firmly fixed in the second nanofiber membrane, so that the stretchable electrode has good stretchability and stability while maintaining conformal adhesion.
[0051] In addition, the stretchable electrode of the present invention has a simple structure, a simple processing process and a low manufacturing cost.
[0052] Therefore, the stretchable electrode of the present invention has excellent stretchability, softness and adhesion, and can be conformally and firmly attached to the surface of various irregularly shaped objects and follow their movement, ensuring the conductive stability of the stretchable electrode. At the same time, the preparation method is simple and the production cost is low.
[0053] It should be noted that the paper-cut structure in the present invention is a Kirigami paper-cut structure.
[0054] Optionally, the thickness of the first flexible nanofiber layer is 40 μm-100 μm; the thickness of the second flexible nanofiber layer is 40 μm-100 μm. Such an arrangement is conducive to improving the overall stretchability and flexibility of the stretchable electrode while ensuring the structural strength of the stretchable electrode.
[0055] It can be understood that in the present invention, the thickness of the first flexible nanofiber layer and the second flexible nanofiber layer can be the same or different, preferably the same. Such an arrangement can better improve the stretching stability of the stretchable electrode.
[0056] Optionally, the first flexible nanofiber layer and the second flexible nanofiber layer are independently selected from any one of a thermoplastic polyurethane (TPU) nanofiber layer and a styrene-butadiene-styrene block copolymer (SBS) nanofiber layer, preferably a thermoplastic polyurethane nanofiber layer. In this way, the first flexible nanofiber layer or the second flexible nanofiber layer has good elasticity and stability, which is conducive to improving the stretchability of the stretchable electrode.
[0057] It can be understood that the first flexible nanofiber layer and the second flexible nanofiber layer in the present invention can be the same or different. The present invention preferably has them be the same. Such a configuration can simplify the process and is beneficial to improving the stretching stability of the stretchable electrode.
[0058] Optionally, the thickness of the liquid metal layer is 3 μm-4 μm. Such a configuration is beneficial for improving the flexibility and stretchability of the stretchable electrode while having excellent conductivity.
[0059] Optionally, the liquid metal layer is selected from a gallium-based liquid metal layer, and the gallium-based liquid metal layer is selected from a liquid gallium-indium alloy layer or a liquid gallium-indium-tin alloy layer, and is further preferably a liquid gallium-indium alloy layer. Such a configuration is conducive to improving the softness, conductivity and stretchability of the stretchable electrode.
[0060] Optionally, the adhesive soft gel is selected from at least one of organic silicone gel, RTVS6100 silicone gel, Caster1010 silicone gel or Hengneng 901 silicone gel, wherein RTVS6100 silicone gel is selected from RTVS6100-5 silicone gel. Such a configuration is conducive to improving the adhesion of the stretchable electrode while not affecting the stretchability and flexibility of the stretchable electrode.
[0061] Optionally, the paper-cut structure is an array structure in the shape of a straight line, an array structure in the shape of a propeller, or an array structure in the shape of an arc, preferably an array structure in the shape of a straight line.
[0062] like Figure 2 As shown, the two adjacent rows of the in-line array structure are preferably arranged in a staggered manner; the two rows of in-line with one row between them are preferably arranged in a matrix. Specifically, the distance between two adjacent in-line arrays in each row is X, 0.1mm≤X≤5mm, preferably 1mm; the line spacing between two adjacent rows is Y, 0.5mm≤Y≤5mm, preferably 1mm-2mm; the length of the in-line is L, 1mm≤L≤10mm, preferably 3mm-5mm.
[0063] At the same time, the present invention also provides a method for preparing a stretchable electrode, comprising the following steps:
[0064] S1, sequentially forming a liquid metal layer and a second flexible nanofiber layer on the surface of the first flexible nanofiber layer to obtain a composite layer;
[0065] S2, processing the composite layer into a paper-cut structure;
[0066] S3, constructing an adhesive soft gel at the nodes of the paper-cut structure, so that the adhesive soft gel is embedded in the surface of the second flexible nanofiber layer to obtain a stretchable electrode.
[0067] In step S1, the method for preparing the composite layer comprises the following steps:
[0068] S11, spinning the first spinning solution by using electrospinning technology to form a first flexible nanofiber layer;
[0069] S12, attaching liquid metal to the surface of the first flexible nanofiber layer to form a liquid metal layer;
[0070] S13, spinning the second spinning solution on the surface of the liquid metal layer by using electrostatic spinning technology to form a second flexible nanofiber layer to obtain the composite layer.
[0071] Specifically, in step S11, the first spinning solution is sucked into a 10mL screw-mouth syringe, a 19G stainless steel dispensing needle is used as the syringe needle, and the syringe is loaded onto the injection pump in the electrospinning machine; the release paper is attached to the surface of the drum in the electrospinning machine, and the distance between the syringe needle and the drum is set, and the positive voltage and negative voltage terminal terminals of the electrospinning machine are connected to the bottom of the dispensing needle and the drum respectively; various parameters of electrospinning are set to obtain the first flexible nanofiber layer.
[0072] It is understandable that when the first flexible nanofiber layer is prepared by electrospinning technology, the release paper is used as an electrospinning collector until step S3 is completed, and then the release paper is removed to obtain a stretchable electrode.
[0073] Optionally, in step S11, the parameters of electrospinning include: an applied positive voltage of 10 kV-20 kV, an applied negative voltage of -1 kV to -8 kV, a drum speed of 200 rpm-1500 rpm, a liquid supply rate of 0.05 mL / min-0.07 mL / min, a distance between the needle and the collecting device of 12 cm-18 cm, a temperature of 25°C-35°C, and an ambient relative humidity of 35%-50%. Such an arrangement is conducive to spinning to form a first flexible nanofiber layer with good air permeability and water permeability, and good stretchability and flexibility.
[0074] In one embodiment, the electrospinning time is 20 min-40 min, preferably 30 min. Such a setting is conducive to controlling the thickness of the first flexible nanofiber layer.
[0075] Optionally, the mass volume ratio of the first spinning solution is 18%-26%. Such a setting is conducive to forming a better spinning effect.
[0076] In one embodiment, the first spinning solution is mixed with a first flexible nanofiber layer precursor material and an organic solvent, and then stirred evenly at room temperature to obtain a first spinning solution, wherein the stirring rate is 200rpm-400rpm and the stirring time is 3h-5h. The mass volume ratio of the first flexible nanofiber layer precursor material to the organic solvent is 20%-30%. Such a setting is conducive to improving the spinning effect.
[0077] Optionally, the first spinning solution is selected from at least one of a thermoplastic polyurethane solution and a styrene-butadiene-styrene block copolymer solution, preferably a thermoplastic polyurethane solution. This arrangement is conducive to improving the stretchability of the first flexible nanofiber layer.
[0078] In one embodiment, the organic solvent is selected from at least one of N,N-dimethylformamide, tetrahydrofuran, and dichloromethane.
[0079] Specifically, when the first spinning solution is selected from a thermoplastic polyurethane solution, the organic solvent is preferably a mixed solvent of tetrahydrofuran and N,N-dimethylformamide, wherein the volume ratio of tetrahydrofuran to N,N-dimethylformamide is 1:1.
[0080] In step S12, liquid metal is attached to the surface of the first flexible nanofiber layer by spraying, coating or scraping to form a liquid metal layer.
[0081] In one embodiment, about 0.5 mL of liquid metal is dropped onto the surface of the first flexible nanofiber layer; a small brush is used to apply the liquid metal on the surface of the first flexible nanofiber layer to form a uniform coating on the surface of the first flexible nanofiber layer.
[0082] In one embodiment, the liquid metal is selected from gallium-based liquid metal, and the gallium-based liquid metal is selected from liquid gallium-indium alloy or liquid gallium-indium-tin alloy, and is more preferably liquid gallium-indium alloy.
[0083] In step S13, the specific steps of spinning the second spinning solution on the surface of the liquid metal layer by using the electrostatic spinning technology to form the second flexible nanofiber layer can refer to the steps in the above step S11.
[0084] Optionally, the electrospinning parameters include: an applied positive voltage of 10kV-20kV, an applied negative voltage of -1kV to -8kV, a drum speed of 200rpm-1500rpm, a liquid supply rate of 0.05mL / min-0.07mL / min, a distance between the needle and the collecting device of 12cm-18cm, a temperature of 25℃-35℃, and an ambient relative humidity of 35%-50%. Such an arrangement is conducive to spinning to form a second flexible nanofiber layer with good air permeability and water permeability, and good stretchability and flexibility.
[0085] In one embodiment, the electrospinning time is 20 min-40 min, preferably 30 min. Such a setting is conducive to controlling the thickness of the second flexible nanofiber layer.
[0086] Optionally, the mass volume ratio of the second spinning solution is 18%-26%.
[0087] In one embodiment, the second spinning solution is mixed with the second flexible nanofiber layer precursor material and the organic solvent, and then stirred evenly at room temperature to obtain the first spinning solution, wherein the stirring rate is 200rpm-400rpm and the stirring time is 3h-5h. The mass volume ratio of the first flexible nanofiber layer precursor material to the organic solvent is 20%-30%. Such a setting is conducive to improving the spinning effect.
[0088] Optionally, the second spinning solution is selected from at least one of a thermoplastic polyurethane solution and a styrene-butadiene-styrene block copolymer solution, preferably a thermoplastic polyurethane solution.
[0089] It can be understood that, in the present invention, the mass volume ratio of the first spinning solution to the second spinning solution is the ratio of the mass of the solute to the volume of the solvent.
[0090] In one embodiment, the organic solvent is selected from at least one of tetrahydrofuran, N,N-dimethylformamide, and dichloromethane. Specifically, when the first spinning solution is selected from a thermoplastic polyurethane solution, the organic solvent is preferably a mixed solvent of tetrahydrofuran and N,N-dimethylformamide, wherein the volume ratio of tetrahydrofuran to N,N-dimethylformamide is 1:1.
[0091] In the present invention, in step S2, the composite layer is cut into a paper-cut structure by using laser cutting technology according to the set paper-cut structure.
[0092] Specifically, the target kirigami paper-cut structure is drawn in the CAD software and saved in DXF format; the DXF file is imported into the laser cutting machine software and the cutting parameters are set; the composite layer is placed on the workbench of the laser cutting machine; the laser head is focused on the surface of the composite layer (the distance is 3cm-5cm), preferably 4cm, and the cutting origin is located, and the laser cutting machine is started to obtain the composite layer of the kirigami paper-cut structure.
[0093] In one embodiment, the laser power of laser cutting is 6W-10W, and the scanning rate is 100mm / s-200mm / s, preferably 150mm / s.
[0094] In step S3, in the step of constructing an adhesive soft gel at the nodes of the paper-cut structure, an adhesive soft gel precursor solution is placed at the nodes of the paper-cut structure and cured to form an adhesive soft gel, wherein the curing temperature is 70°C-90°C and the curing time is 10min-20min.
[0095] Specifically, the adhesive soft gel precursor solution is loaded into a 2mL syringe; a 23G dispensing needle is installed on the syringe, and the needle is placed about 0.2mm-1mm above the node of the paper-cut structure, preferably 0.5mm. The adhesive soft gel precursor solution in the syringe will naturally fall and infiltrate the surface of the second flexible nanofiber layer at the node. According to this method, one drop of adhesive soft gel precursor solution is applied to the surface of the second flexible nanofiber layer at each node in the shear structure in turn, and then transferred to a constant temperature heating table for heating and curing to form an adhesive soft gel; the above steps can be repeated multiple times as needed, and finally an adhesive soft gel embedded in the surface of the second flexible nanofiber layer is obtained to obtain a stretchable electrode.
[0096] In one embodiment, the adhesive soft gel precursor solution is selected from at least one of RTVS6100 silicone gel, Caster1010 silicone gel or Hengneng 901 silicone gel, wherein RTVS6100 silicone gel is selected from RTVS6100-5 silicone gel. Specifically, the adhesive soft gel precursor solution can be obtained by mixing transparent organic silicone gel RTVS6100-5 (A) and RTVS6100-5 (B) in a ratio of 1:1 and stirring them thoroughly.
[0097] It can be understood that in the present invention, the first flexible nanofiber layer is prepared by electrospinning technology as the flexible base layer, the second flexible nanofiber layer is used as the encapsulation layer, and a single liquid metal is used as the conductive layer to form a sandwich structure. The paper-cut structure can be quickly obtained by using laser cutting technology, and the adhesive soft gel is constructed in the paper-cut structure by drop coating and thermal curing. Compared with the existing technology, the materials involved in the present invention are common and easy to obtain, the processing process is simple, and the production cost is low.
[0098] In addition, the present invention also provides an application of the stretchable electrode as described above in wearable electronic products, electronic skin, implantable medical electronic devices or soft robots.
[0099] In one embodiment, the stretchable electrode can be used as a flexible wire or a flexible electric heater when connected to an external circuit. Specifically, when the stretchable electrode is used for a flexible electric heater, the temperature rises from 34.1°C to 41.5°C after heating for 5 seconds at a low voltage of 1V, and the heat is kept stable during deformation. Therefore, the stretchable electrode of the present invention has good adhesion and heating performance.
[0100] The stretchable electrode, its preparation method and application will be further described below through the following specific examples. However, those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, they are carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.
[0101] Example 1
[0102] 7.5 g of thermoplastic polyurethane, 15 mL of N,N-dimethylformamide and 15 mL of tetrahydrofuran were added into a beaker and stirred evenly at room temperature with a magnetic stirrer, wherein the speed of the magnetic stirrer was 300 rpm and the stirring time was 4 h to obtain a thermoplastic polyurethane spinning solution; the silicone gel RTVS6100-5 (A) and RTVS6100-5 (B) were mixed in a mass ratio of 1:1 and stirred evenly to obtain an adhesive soft gel precursor solution.
[0103] Two 10mL screw-mouth syringes were used to absorb the thermoplastic polyurethane spinning solution obtained above respectively, and a stainless steel dispensing needle (19G) was installed on the screw-mouth syringe; then the two screw-mouth syringes were fixed on the injection pump in the electrospinning machine (TEADFS-100, Beijing Xinrui Baina Technology Co., Ltd.), and the positive voltage interface of the electrospinning machine was fixed to the bottom of the stainless steel dispensing needle; a layer of release paper was pasted on the drum in the electrospinning machine as an electrospinning collector, and the position of the injection pump was adjusted so that the distance from the stainless steel dispensing needle to the drum was 15cm; finally, the working parameters of the electrospinning machine were set, wherein the external positive voltage was 11Kv, the external negative voltage was -3kV, the liquid supply rate was 0.06mL / min, the drum speed was 500rpm, the temperature was 30°C, the relative humidity of the environment was 40%, and the electrospinning machine was started and operated for 30min, and then the electrospinning machine was turned off to obtain a first flexible nanofiber layer with a thickness of 60μm.
[0104] The liquid gallium-indium alloy is added into the straw, and then about 0.5 μm of the liquid gallium-indium alloy is dropped onto the surface of the first flexible nanofiber layer. The liquid gallium-indium alloy is evenly brushed onto the first flexible nanofiber layer using a fine brush to form a liquid gallium-indium alloy layer with a thickness of 3 μm. Figure 4 shown.
[0105] Then, the electrospinning machine was started again, and the above electrospinning process was repeated for 30 minutes to form a second flexible nanofiber layer with a thickness of 60 μm, thereby obtaining a composite layer.
[0106] according to Figure 2The paper-cut structure shown, wherein the paper-cut parameters are L=5 mm, X=1 mm, Y=1 mm, the laser power is set to 7.5 W, the scanning rate is set to 150 mm / s, and the laser vector mode is used to laser cut the composite layer to obtain a sheared structure.
[0107] The adhesive soft gel precursor solution obtained above is loaded into a 2mL syringe, and then a 23G dispensing needle is installed on the syringe, and the needle is placed about 0.5mm above the node of the shear structure. The adhesive soft gel precursor solution in the syringe will naturally fall and infiltrate the surface of the second flexible nanofiber layer corresponding to the node of the shear structure. In this way, one drop of adhesive soft gel precursor solution is applied to each node of the shear structure in turn. Then transfer the sample to a hot plate at 80°C and heat and cure for 15 minutes; after curing, repeat the dispensing and heat curing steps twice, and an adhesive soft gel embedded in the first flexible nanofiber layer can be constructed at the node of the shear structure, such as Figure 5 As shown, finally peel off the release paper to obtain Figure 1 The stretchable electrode shown.
[0108] Example 2
[0109] Compared with Example 1, Example 2 differs only in that the various parameters of electrospinning include: an applied positive voltage of 11 kV, an applied negative voltage of -1 kV, a drum rotation speed of 600 rpm, a liquid supply rate of 0.05 mL / min, a distance between the needle and the collecting device of 12 cm, a temperature of 25°C, and an ambient relative humidity of 35%; in the step of spinning to form the first flexible nanofiber layer, the electrospinning time is 25 min, the curing temperature is 75°C, the curing time is 18 min, and the other conditions are the same, to obtain a stretchable electrode, wherein the thickness of the first flexible nanofiber layer is 40 μm, and the thickness of the second flexible nanofiber layer is 47 μm.
[0110] Example 3
[0111] Compared with Example 1, Example 3 differs only in that the various parameters of electrospinning include: an applied positive voltage of 18 kV, an applied negative voltage of -5 kV, a drum rotation speed of 400 rpm, a liquid supply rate of 0.07 mL / min, a distance between the needle and the collecting device of 18 cm, a temperature of 35°C, and an ambient relative humidity of 45%; in the step of spinning to form the first flexible nanofiber layer, the electrospinning time is 50 min, the curing temperature is 85°C, the curing time is 10 min, and the other conditions are the same, to obtain a stretchable electrode, wherein the thickness of the first flexible nanofiber layer is 100 μm, and the thickness of the second flexible nanofiber layer is 70 μm.
[0112] Example 4
[0113] The only difference between Example 4 and Example 1 is that the paper cutting parameters L=3 mm, X=1 mm, Y=1 mm, and the other conditions are the same, and a stretchable electrode is obtained.
[0114] Example 5
[0115] The only difference between Example 5 and Example 1 is that the paper cutting parameters L=3 mm, X=1 mm, Y=2 mm, and the other conditions are the same, and a stretchable electrode is obtained.
[0116] Example 6
[0117] The only difference between Example 6 and Example 1 is that the paper cutting parameters L=3 mm, X=3 mm, Y=2 mm, and the other conditions are the same, and a stretchable electrode is obtained.
[0118] Example 7
[0119] The only difference between Example 7 and Example 1 is that styrene-butadiene-styrene block copolymer is used instead of thermoplastic polyurethane, and liquid gallium indium tin alloy is used instead of liquid gallium indium alloy. Other conditions are the same, and a stretchable electrode is obtained.
[0120] Comparative Example 1
[0121] The only difference between Comparative Example 1 and Example 1 is that it does not contain the step of processing the composite layer into a paper-cut structure, that is, the adhesive soft gel precursor solution obtained above is directly applied to the surface of the second flexible nanofiber layer of the composite layer, and the other conditions are the same to obtain a stretchable electrode.
[0122] Comparative Example 2
[0123] Comparative Example 2 is different from Example 1 only in that the step of constructing an adhesive soft gel embedded in the second flexible nanofiber layer at the node of the shear structure is not included, and the other conditions are the same to obtain a stretchable electrode. The stretchable electrode of this comparative example has no adhesion and cannot be adhered to the surface of other objects and follow the movement.
[0124] Application Example 1
[0125] A first flexible nanofiber layer with a thickness of 60 μm is prepared according to the method of Example 1; the surface of the first flexible nanofiber layer is divided into a first area and a second area connected to the periphery of the first area, about 0.5 ml of liquid gallium-indium alloy is dripped onto the surface of the first flexible nanofiber layer, and the liquid gallium-indium alloy is evenly brushed on the surface of the second area of the first flexible nanofiber layer with a fine brush to form a liquid gallium-indium alloy layer, and at the same time, a chip LED lamp is placed in the first area on the surface of the first flexible nanofiber layer, so that the left and right electrodes of the chip LED lamp are connected to the liquid gallium-indium alloy layers on both sides of the first area; then, spinning is performed according to the method of Example 1 to form a second flexible nanofiber layer with a thickness of 60 μm to obtain a composite layer.
[0126] according to Figure 3 The paper-cut structure shown, wherein the paper-cut parameters are L=5 mm, X=1 mm, Y=1 mm, the laser power is set to 7.5 W, the scanning rate is set to 150 mm / s, and the laser vector mode is used to laser cut the composite layer to obtain a sheared structure.
[0127] According to the method of Example 1, an adhesive soft gel embedded in the first flexible nanofiber layer is constructed at the node of the shear structure to obtain a stretchable electrode with a patch LED lamp.
[0128] The stretchable electrode with the SMD LED lamp prepared in this application example is connected to an external circuit to demonstrate its ability to adhere to the surface of irregular objects as a flexible wire and maintain stable operation during deformation. Specifically, the stretchable electrode with the SMD LED lamp is attached to the surface of the silicone bellows, and then an ordinary commercial wire is welded to the copper sheet, and the copper sheet is inserted into the liquid gallium-indium alloy layer of the stretchable electrode to connect it to the liquid gallium-indium alloy; the other end of the commercial wire is connected to a DC power supply with a voltage of 3.3V. Fig.13 As shown, the stretchable electrode can conformally adhere to the irregularly shaped surface of the silicone bellows, and maintain conformal adhesion and stable power supply when the bellows undergoes compression, stretching, and torsion. Therefore, the high adaptability and stability of the stretchable electrode of the present invention demonstrates its application potential in the field of stretchable wires.
[0129] The mechanical and electrical properties of the stretchable electrodes prepared in Example 1 and Examples 4-6 were tested. The test results are as follows: Figure 6-10 As shown, the specific testing method is as follows: first, insert the copper sheet with the enameled wire into the two ends of the stretchable electrode, and then use the clamp of the mechanical testing machine to clamp the two ends of the stretchable electrode; then, connect the enameled wire to the LCR meter; then use the mechanical testing machine to test the mechanical properties of the stretchable electrode, and use the LCR meter to test the electrical properties of the stretchable electrode.
[0130] from Figure 6 It can be seen that the elongation at break of the stretchable electrode of Example 1 reaches 1085%, and there is no obvious stress increase within the tensile strain range of 140%, indicating that the synergistic cooperation of the first flexible nanofiber layer, the second flexible nanofiber layer and the liquid metal layer can enable the stretchable electrode to exert excellent stretchability and compliance. Figure 7 It can be seen that during the stretching to 1085%, the stretchable electrode always remains conductive, and within the stretching range of 110%, the resistance of the stretchable electrode has basically not changed, and Figure 8 It can be seen that after 3000 cycles of stretching at 50% strain, the resistance of the stretchable electrode remains stable, which shows that the stretchable electrode of the present invention has excellent and stable conductivity.
[0131] from Fig. 9 It can be seen that the elongation at break of the stretchable electrodes of Example 4, Example 5, and Example 6 are 637%, 364%, and 514%, respectively, and they all show good compliance within a strain range of 30%. Fig.10 It can be seen that the resistance values of the stretchable electrodes of Examples 4, 5, and 6 remain stable within the 30% tensile strain range, and then show different resistance change trends. The above results show that the paper-kirigami adhesive stretchable electrodes have good stretchability, conductivity, and compliance, and the mechanical and electrical properties of the electrodes can be adjusted by changing the parameters L, X, and Y of the paper-kirigami structure.
[0132] from Figure 11-12 It can be seen that the stretchable elastic modulus prepared in Comparative Example 1 is 0.875 MPa, which is far higher than the stretchable electrode of the embodiment of the present invention, and the resistance changes by 2.4% when stretched to 30% elongation, and changes by 37.5% when stretched to 200% elongation, and the resistance stability decreases.
[0133] At the same time, the stretchable electrode prepared in Example 1 was connected to an external circuit to demonstrate its application capability as a stretchable heater. Specifically, the stretchable electrode was adhered to the wrist joint, and then a copper sheet was inserted into the liquid gallium-indium alloy layer of the stretchable electrode to connect it to the liquid gallium-indium alloy layer; the output pin of the DC power supply was clamped on the copper sheet and the power supply voltage was set to 1V. Fig.14As shown, the stretchable electrode can increase the temperature of the wearing area from 34.1°C to 41.5°C within 5 seconds, and maintain conformal adhesion and stable heating when the wrist is bent and deformed. Therefore, the stretchable electrode of this embodiment can be conformally attached to the surface of other objects and quickly heat the target object at a low voltage, which shows that the stretchable electrode of the present invention has potential application value in the fields of soft robots, electronic skin and wearable electrothermal therapy equipment.
[0134] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0135] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A stretchable electrode, characterized in that: The stretchable electrode includes a first flexible nanofiber layer and a liquid metal layer and a second flexible nanofiber layer stacked in sequence on the surface of the first flexible nanofiber layer. The stretchable electrode is a paper-cut structure, and an adhesive soft gel is provided at the nodes of the paper-cut structure, and the adhesive soft gel is embedded in the surface of the second flexible nanofiber layer.
2. The stretchable electrode according to claim 1, characterized in that The thickness of the first flexible nanofiber layer is 40 μm-100 μm; And / or, the thickness of the second flexible nanofiber layer is 40 μm-100 μm; And / or, the thickness of the liquid metal layer is 3 μm-4 μm.
3. The stretchable electrode according to claim 1, characterized in that The first flexible nanofiber layer and the second flexible nanofiber layer are independently selected from any one of a thermoplastic polyurethane nanofiber layer and a styrene-butadiene-styrene block copolymer nanofiber layer; And / or, the liquid metal layer is selected from a gallium-based liquid metal layer; And / or, the adhesive soft gel is selected from at least one of RTVS6100 silicone gel, Caster1010 silicone gel or Hengnian 901 silicone gel.
4. The stretchable electrode according to claim 1, characterized in that The paper-cut structure is an array structure formed in a straight line, an array structure formed in a propeller shape, or an array structure formed in an arc shape.
5. A method for preparing a stretchable electrode according to any one of claims 1 to 4, characterized in that: The following steps are involved: sequentially forming a liquid metal layer and a second flexible nanofiber layer on the surface of the first flexible nanofiber layer to obtain a composite layer; Processing the composite layer into a paper-cut structure; An adhesive soft gel is constructed at the nodes of the paper-cut structure so that the adhesive soft gel is embedded on the surface of the second flexible nanofiber layer to obtain a stretchable electrode.
6. The method for preparing a stretchable electrode according to claim 5, characterized in that: The preparation method of the composite layer comprises the following steps: Spinning the first spinning solution by electrospinning technology to form a first flexible nanofiber layer; Adhering liquid metal to the surface of the first flexible nanofiber layer to form a liquid metal layer; The second spinning solution is spun on the surface of the liquid metal layer by using electrostatic spinning technology to form a second flexible nanofiber layer to obtain the composite layer.
7. The method for preparing a stretchable electrode according to claim 6, characterized in that: In the step of spinning the first spinning solution by electrospinning technology to form the first flexible nanofiber layer, the electrospinning parameters include: an applied positive voltage of 10 kV-20 kV, an applied negative voltage of -1 kV to -8 kV, a drum speed of 200 rpm-1500 rpm, a liquid supply rate of 0.05 mL / min-0.07 mL / min, a distance between the needle and the collecting device of 12 cm-18 cm, a temperature of 25 ° C-35 ° C, and an ambient relative humidity of 35%-50%; And / or, the mass volume ratio of the first spinning solution is 18%-26%, and the first spinning solution is selected from at least one of a thermoplastic polyurethane solution and a styrene-butadiene-styrene block copolymer solution.
8. The method for preparing a stretchable electrode according to claim 6, characterized in that: In the step of using the second spinning solution to form a second flexible nanofiber layer on the surface of the liquid metal layer using an electrospinning technique, the electrospinning parameters include: an applied positive voltage of 10 kV to 20 kV, an applied negative voltage of -1 kV to -8 kV, a drum rotation speed of 200 rpm to 1500 rpm, a liquid supply speed of 0.05 mL / min to 0.07 mL / min, a distance between the needle and the collecting device of 12 cm to 18 cm, a temperature of 25° C. to 35° C., and an ambient relative humidity of 35% to 50%; And / or, the mass volume ratio of the second spinning solution is 18%-26%, and the second spinning solution is selected from at least one of a thermoplastic polyurethane solution and a styrene-butadiene-styrene block copolymer solution.
9. The method for preparing a stretchable electrode according to claim 5, characterized in that: In the step of processing the composite layer into a paper-cut structure, the composite layer is cut into the paper-cut structure by using a laser cutting technology according to the set paper-cut structure; And / or, in the step of constructing an adhesive soft gel at the nodes of the paper-cut structure, an adhesive soft gel precursor solution is placed at the nodes of the paper-cut structure and cured to form an adhesive soft gel, wherein the curing temperature is 70°C-90°C and the curing time is 10min-20min.
10. Use of the stretchable electrode according to any one of claims 1 to 4 in wearable electronic products, electronic skin or soft robots.
Citation Information
Cited By
Octopus bionic sucker flexible negative voltage electrode patch for nerve electrical regulation and control
CN121243611A
